Initial establishment of the irish strain of Microctonus aethiopoides in New Zealand - Gerard, P.J.; Eden, T.M.; Hardwick, S.; Mercer, C.F.; Slay, M.W.A.; Wilson, D.J. (New Zealand Plant Protection, 2007)
Four experimental releases of the parthenogenetic strain of Microctonus aethiopoides from Ireland were made in early 2006 in the Waikato Manawatu (two sites) and Hawkes Bay By early winter establishment was confirmed at all sites with parasitism levels exceeding 10 in the target host Sitona lepidus a serious pest of white clover in New Zealand Subsequent monitoring revealed considerable betweensite variation At the Hawkes Bay and Manawatu Feilding sites where overwintering weevil adults were still present in October over 30 parasitism was found in newly emerged weevils in December 2006 In contrast at the Waikato and Manawatu Bulls sites where there was no overlap of host generations parasitism was below detectable levels during spring and early summer but recovered subsequently The Irish M aethiopoides appears to have four generations a year and diapauses over winter as a first instar larva Following the initial success releases have commenced in other regions